Meningkatkan Daya Saing Terasi Melalui Strategi Pemasaran Digital: Pendampingan Usahawan Oleh-Oleh Khas Desa Sentang, Batu Bara - Yeni Absah; Beby Karina F. Sembiring; Endang Sulistya Rini; Elperida J. Sinurat; Dina Arfianti Siregar; Agus Edi Rangkuti; Harris Pinagaran Nasution; Hidayat Nasution; Florence Sirait; Moudy Fitria Respati; Tengku Muhammad Adriansyah; Alexander Tan; Badikenita br. Sitepu (Jurnal Pengabdian Pada Masyarakat METHABDI, 2026)
Small-scale industries, particularly those involved in the processing of terasi (shrimp paste), play a vital role in regional economic development and improving community welfare, in particular as a traditional souvenir. However, this industry faces various challenges, including limited marketing opportunities, reliance on conventional technology, difficulty in securing capital, an unreliable supply of raw materials, and a lack of skilled labour. This article aims to analyze the terasi industry in Sintang Village, Nibung Hangus Sub-district, Batu Bara District, North Sumatra Province, which is widely recognized as a center of production of high-quality, preservative-free terasi. Through training and mentoring, we identified and addressed the challenges faced by terasi entrepreneurs. The methods used included lectures, discussions, and practical sessions on creating social media accounts for product promotion. The results of the activity demonstrated high enthusiasm among participants in attending the training, which is expected to enhance marketing competencies and expand market reach. The conclusions from this activity underscore the importance of continuous training to support terasi entrepreneurs, as well as the potential for follow-up initiatives in other areas of business management.